Metastasis-associated fibroblasts promote angiogenesis in metastasized pancreatic cancer via the CXCL8 and the CCL2 axes - Pausch, Thomas; Aue, Elisa; Wirsik, Naita Maren; Freire Valls, Aida; Shen, Ying; Radhakrishnan, Praveen; Hackert, Thilo; Schneider, Martin; Schmidt, Thomas (Scientific reports, 2020)
The characteristic desmoplastic stroma of pancreatic ductal adenocarcinoma (PDAC) is a key contributor to its lethality. This stromal microenvironment is populated by cancer-associated fibroblasts (CAFs) that interact with cancer cells to drive progression and chemo-resistance. Research has focused on CAFs in the primary tumour but not in metastases, calling into question the role of analogous metastasis-associated fibroblasts (MAFs). We infer a role of MAFs in murine hepatic metastases following untargeted treatment with the anti-angiogenic drug sunitinib in vivo. Treated metastases were smaller and had fewer stromal cells, but were able to maintain angiogenesis and metastasis formation in the liver. Furthermore, sunitinib was ineffective at reducing MAFs alongside other stromal cells. We speculate that cancer cells interact with MAFs to maintain angiogenesis and tumour progression. Thus, we tested interactions between metastatic pancreatic cancer cells and fibroblasts using in vitro co-culture systems. Co-cultures enhanced fibroblast proliferation and induced angiogenesis. We identify carcinoma-educated fibroblasts as the source of angiogenesis via secretions of CXCL8 (aka IL-8) and CCL2 (aka MCP-1). Overall, we demonstrate that metastasis-associated fibroblasts have potential as a therapeutic target and highlight the CXCL8 and CCL2 axes for further investigation.